ANALISIS STRATEGI KOMUNIKASI PEMASARAN PRODUK LAPTOP DALAM MENARIK MINAT PEMBELI STUDI PADA SOSIAL MEDIA FACEBOOK DICKYCOM - Abdillah, Wiwit Hamzah; Purwanti, Angel (SCIENTIA JOURNAL, 2022)
Digital marketing communication is a combination of understanding of digital marketing in marketing communications with digital marketing, which is a place or stage where businesspeople provide information, persuade, and influence customers about services and products marketed by utilizing social media and the internet. The purpose of this research is to find out and analyze the marketing communication strategy of laptop products in attracting buyers through social media facebook DICKYcom. The type of research used in this research is descriptive qualitative research. The results showed that the use of marketing communication strategies, namely the marketing mix; product, price, place and promotion are able to attract buyers. The conclusion shows that the strategy used is sales promotion by creating advertisements and displaying various gaming laptop products with special specifications by utilizing the online media Facebook and it is found that visual communication factors and recommendations also play a very important role in increasing the Dicky.com facebook account brand.